ANALISIS YURIDIS TERHADAP KEPASTIAN HUKUM DALAM PERMOHONAN PENGURANGAN ANGSURAN PPH PASAL 25 BERDASARKAN PERATURAN DIREKTUR JENDERAL PAJAK NOMOR PER-11/PJ/2025 - Poniah Tanjung (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2026)
Tax is the main source of state revenue that plays an important role in financing national development, one of which is through Income Tax (PPh) Article 25 which is paid with a monthly installment mechanism. Under certain conditions, Taxpayers are given the right to apply for a reduction in PPh Article 25 installments. Provisions regarding this mechanism are regulated in the Regulation of the Director General of Taxes Number PER-11/PJ/2025 whose implementation is integrated through a digital-based tax administration system (Coretax). This research focuses on two problem formulations, namely: how is the mechanism to obtain legal certainty in the application of the provisions for reducing PPh Article 25 installments based on PER-11/PJ/2025; and what are the legal implications of implementing the PPh Article 25 installment reduction policy on the rights and obligations of Taxpayers. The research method used is normative juridical research supported by empirical data with a statutory and conceptual approach, using primary, secondary, and tertiary legal materials analyzed qualitatively. The results of the study indicate that normatively PER-11/PJ/2025 has provided a legal basis and procedural framework for submitting applications for reductions in Article 25 Income Tax installments through the Coretax system. However, in its implementation there is still potential for legal uncertainty stemming from technical aspects of the system, administrative burdens, and differences in the assessment of the fairness of financial data by the tax authorities. The implementation of this policy has legal implications for the implementation of taxpayers' rights and obligations, particularly regarding administrative obligations, transparency of decisions, legal protection, and the balance between the authority of the tax authorities and taxpayers' rights. This study concludes that legal certainty in the implementation of PER-11/PJ/2025 has not been fully realized optimally, so it is necessary to strengthen assessment standards, consistency of application, and improve the quality of system-based tax administration to ensure legal protection and justice for taxpayers.